Serious game for lean layout planning: a proposal for involving company staff within the design process. (12th June 2021) - Cantini, Alessandra; Carlo, Filippo De; Tucci, Mario
Planning the layout of a company directly affects the performance of a production system. To generate an effective layout solution, it is fundamental to involve both design experts and company staff at all stages of the design process. This paper presents a novel lean layout planning system to engage company staff in the research of the layout solution. A two-step process was followed: first, a literature-based approach was applied to get a prototype layout, then a strategy to engage the company's staff in the achievement of the final solution was proposed. The article describes the proposed strategy and shows how the layout changes with or without the involvement of skilled staff. A case study of a leather bags manufacturing plant is also presented. The case study results highlight how the proposed procedure can be helpful in achieving a solution that better satisfies workers and makes employees accept working changes.